Globalisierung der Universität: Veränderungen in der Forschungslandschaft Großbritanniens - Hellen, J. Anthony (ERDKUNDE, 1997)
Published in December 1996, a comprehensive Research Assessment Exercise ranked the research performance of all British universities at subject/departmental level for the period 1992-1996. In the context of recent changes in the British university system and growing competition for and selectivity of research funding, this article reviews the fall-out following publication of research league tables, before considering the performance of British geography departments. Finally, it develops the theme of globalization, competition and market forces as agents of change in the university sector.